Implementation of School Policy in Realizing the Character Education Program at SMA Negeri 1 Kuta Baro Aceh Besar - Fikri, Ahlul; Muluk, Safrul; Silahuddin, Silahuddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Creating students who have good character is the main goal of national education, and one effort to create this goal is by implementing character education programs in schools. In this case, the school principal as a leader has an important role in taking policies to implement character education programs in schools. The aim of this research is to determine the implementation of school policies in realizing character education at SMA Negeri 1 Kuta Baro Aceh Besar. This research uses a qualitative descriptive approach. Data was collected using observation, documentation and interview methods. Next, the data was analyzed through stages of data reduction and drawing conclusions. The results of this research show that the implementation of school policies in realizing character education at SMA Negeri 1 Kuta Baro Aceh Besar was carried out by involving multi-stakeholders, including teachers, school committees, students and parents. Some of the character education programs implemented at SMA Negeri 1 Kuta Baro Aceh Besar are complete reading of the Al-Qur'an, zhuha prayer activities every morning, congregational zhuhur prayers, Islamic studies, yellow book meudrah, tahsin/tahfiz of the Al-Qur'an , reading Yasin and reading zikr regularly every Friday. The implementation of the character education program at SMA Negeri 1 Kuta Baro is the school's effort to realize Islamic culture in students' daily lives. The program is designed and implemented to support the formation of students' character. The implementation of the character education program as a school culture at SMA Negeri 1 Kuta Baro involves all elements of the school, including teachers and education staff, who play an active role in monitoring and evaluating its implementation.